2013
DOI: 10.2147/cmar.s45957
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD19 in B-cell lymphoma: emerging role of SAR3419

Abstract: Non-Hodgkin lymphoma symbolizes a heterogeneous group of diseases resulting from malignant transformation of lymphocytes with differing patterns of behavior and responses to treatment. The potential curability of non-Hodgkin lymphoma differs among the various histologic subtypes and is associated in part with the stage at presentation. CD19 antigen is a type I transmembrane glycoprotein belonging to the immunoglobulin Ig superfamily. CD19 is specifically expressed in normal and neoplastic B-cells. Recent study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Although the initial clinical evaluation of CAR-T cells focused on B cell non-Hodgkin’s lymphoma (B-NHL) (Kochenderfer et al, 2010 ; Till et al, 2008 ), the most striking outcomes have been obtained in B-ALL by targeting CD19, a B cell-lineage antigen expressed on the surface of normal B cells and many malignant B cells (Scheuermann and Racila, 1995 ; Depoil et al, 2008 ). Another pan-B cell marker, CD20, is also an attractive target for CAR-T cell therapy in B cell malignancies (Raufi et al, 2013 ). Preliminary clinical trials evaluating anti-CD20 CAR-T cells for patients with B-NHL revealed minimal toxicities with modest efficacy (Wang et al, 2014 ; Till et al, 2008 , 2012 ), until recently a phase IIa clinical trial performed at PLAGH demonstrated an objective remission rate (ORR) of 82% (complete remission (CR) 6/11, partial remission (PR) 3/11) with well-tolerated toxicity (Zhang et al, 2016a ).…”
Section: Clinical Outcomes Of Hematological Malignanciesmentioning
confidence: 99%
“…Although the initial clinical evaluation of CAR-T cells focused on B cell non-Hodgkin’s lymphoma (B-NHL) (Kochenderfer et al, 2010 ; Till et al, 2008 ), the most striking outcomes have been obtained in B-ALL by targeting CD19, a B cell-lineage antigen expressed on the surface of normal B cells and many malignant B cells (Scheuermann and Racila, 1995 ; Depoil et al, 2008 ). Another pan-B cell marker, CD20, is also an attractive target for CAR-T cell therapy in B cell malignancies (Raufi et al, 2013 ). Preliminary clinical trials evaluating anti-CD20 CAR-T cells for patients with B-NHL revealed minimal toxicities with modest efficacy (Wang et al, 2014 ; Till et al, 2008 , 2012 ), until recently a phase IIa clinical trial performed at PLAGH demonstrated an objective remission rate (ORR) of 82% (complete remission (CR) 6/11, partial remission (PR) 3/11) with well-tolerated toxicity (Zhang et al, 2016a ).…”
Section: Clinical Outcomes Of Hematological Malignanciesmentioning
confidence: 99%
“…CD19 is a desirable target for ADC therapy because it is quickly internalized upon antibody binding [ 50 ]. SAR3419 is a novel ADC which combines the humanized anti-CD19 monoclonal antibody with the tubulin inhibitor DM4.…”
Section: Novel Antibodies and Antibody-drug Conjugates Directed Agmentioning
confidence: 99%
“…It has threefold higher expression in mature B cells compared with immature B cells (57) and is one of the earliest B cell restricted antigens. It plays an important role in maintaining balance between immunity and autoimmunity.…”
Section: Cd19mentioning
confidence: 99%